Precisely Control Relationship between Sulfur Vacancy and H Absorption for Boosting Hydrogen Evolution Reaction - Jin, Jing; Wang, Xinyao; Hu, Yang; Zhang, Zhuang; Liu, Hongbo; Yin, Jie; Xi, Pinxian (Nano-Micro Letters, 2024)
Effective and robust catalyst is the core of water splitting to produce hydrogen. Here, we report an anionic etching method to tailor the sulfur vacancy (VS) of NiS2 to further enhance the electrocatalytic performance for hydrogen evolution reaction (HER). With the VS concentration change from 2.4% to 8.5%, the H* adsorption strength on S sites changed and NiS2-VS 5.9% shows the most optimized H* adsorption for HER with an ultralow onset potential (68 mV) and has long-term stability for 100 h in 1 M KOH media. In situ attenuated-total-reflection Fourier transform infrared spectroscopy (ATR-FTIRS) measurements are usually used to monitor the adsorption of intermediates. The S- H* peak of the NiS2-VS 5.9% appears at a very low voltage, which is favorable for the HER in alkaline media. Density functional theory calculations also demonstrate the NiS2-VS 5.9% has the optimal |ΔGH*| of 0.17 eV. This work offers a simple and promising pathway to enhance catalytic activity via precise vacancies strategy. Highlights: 1 The Ar plasma etching strategy was introduced to homogeneously distributed S-vacancies (VS) into the NiS2 nanosheets (NiS2-VS). 2 Build the relationship between sulfur vacancy and H absorption and find that NiS2-VS 5.9% performs outstanding hydrogen evolution reaction performance and remarkable stability.